Prevalence of endometriosis in women undergoing laparoscopic surgery for various gynaecological indications at a Jordanian referral centre: gaining insight into the epidemiology of an important women's health problem - Nadia Muhaidat; Shawqi Saleh; Kamil Fram; Mohammed Nabhan; Nadia Almahallawi; Saif Aldeen Alryalat; Mutasem Elfalah; Mohammed Elfalah (BMC, 2021)
Abstract Background Endometriosis is a considerable health challenge for women of reproductive age. Information about its prevalence in the Jordanian population is sparse. The objective of this research was to evaluate the presence of endometriosis in gynaecological patients undergoing laparoscopic surgery for various indications and to correlate the finding of endometriosis with variables, including patient demographics, obstetric history, type, and indication of laparoscopic procedure. Methods A retrospective cohort study involving 460 women who underwent different laparoscopic procedures for a variety of indications was conducted in the Department of Obstetrics and Gynaecology in Jordan University Hospital, a tertiary referral hospital in Jordan, between January 2015 and September 2020. Results The prevalence of endometriosis in this patient group was higher than that of the general population (13.7% vs. 2.5%), and the mean age at diagnosis (31.9 years) was younger than the general population's age of peak incidence (35-45 years). It was significantly higher in women with lower numbers of pregnancies (p = 0.01) and a lower number of Caesarean sections (p = 0.05) and in those where the indication for surgery was related to decreased fertility or pelvic pain (p = 0.02). Women with high parity or where the surgery's indication suggested normal fertility, such as family planning, were less likely to have endometriosis. Conclusion To our knowledge, this is the first Jordanian study to assess the prevalence of endometriosis in women undergoing gynaecological laparoscopy. This study suggests that the epidemiology of endometriosis in this region follows similar trends to what has been previously documented in international literature, while emphasizing the need for further research into this important women's health issue in this part of the world.